Elaboration de nouveaux matériaux lignocellulosiques pour une étude comparative d’adsorption de micropolluants en milieu aqueux. - RECHACHE Mustapha (My University, 2012)
This study was devoted to the promotion of a lignocellulosic waste namely wood sawdust through a simple chemical functionalization in order to apply to the removal of anionic dyes. A comparative study was conducted on the adsorption of two dyes (thiazole yellow and the bright yellow) with the lignocellulosic material derived from the sawdust. In this study the parameters governing the adsorption such as pH, temperature, contact time were carefully analyzed. The results obtained show that the material can be used with efficiency for removing anionic dyes and in addition it can be completely regenerated.
Keywords: adsorption, chemical functionalization, thiazole yellow, bright yellow,